Direct somatic embryogenesis and plant regeneration in Garcinia indica Choiss - Thengane, Shubhada Ratnakar; Deodhar, Swapna R.; Bhosle, S. V.; Rawal, S. K. (Current Science, 2006)
Direct somatic embryogenesis without an intervening callus phase was induced from immature seeds of Gar- cinia indica Choiss. Woody plant medium supplemented with 6-benzyl amino purine (BAP) (4.44-22.19 mu m) alone or in combination with a-naphthaleneacetic acid (2.69 mu m) produces somatic embryos within a period of 2-3 weeks with 80% frequency. Embryo induction was observed all over the explant surface. Origin of the embryo was confirmed histologically from sub-epidermal layer of the seed. Maturation of these embryos was achieved after 12 weeks of culture on a medium containing BAP (16.08 mu m) in combination with indole-3-acetic acid (2.85-5.71 mu m) and/or kinetin (4.65 mu m). About 75% of the regenerated somatic embryos germinated into complete plantlets. The plantlets were acclimatized successfully with 92% survival in greenhouse.
Keywords: Garcinia indica; guttifereae; seeds; somatic embryos

De novo shoot regeneration from root cultures of garcinia indica choiss - Deodhar, Swapna R.; Thengane, R. J.; Thengane, Shubhada Ratnakar (Indian Journal of Experimental Biology, 2008)
Roots of plantlets of Garcinia indica when cultured for long time on half strength MS medium supplemented with BAP (0.44-2.22 mu M) showed production of de novo shoots. Roots attached to mother plant showed more number of shoots, while excised root segments produced lesser shoots. Shoots (0.5-0.8 cm) were transferred to elongation medium consisting of Woody Plant Medium (WPM) supplemented with BAP (4.44-22.69 mu M), IAA (5.71 mu M and kinetin (4.65 mu M). It was observed that shoot length increased to 1-2 cm. WPM medium supplemented with NAA (2.69-10.74 mu M) and IBA (4.90 mu M) induced rooting within 20-25 days. Using the present protocol, 20-25 plantlets could be regenerated from single root explant within 3 to 4 months. The protocol has potential for large scale production of elite plants.
Keywords: Garcinia indica; guttifereae; organogenesis; roots; shoots